Route Optimization System - Zulkifli, Abdul Hayy (universiti teknologi petronas, 2005)
This final year project is focused on creating a route generation application that can find the best route on a real road network. The distinct lack of route optimization systems or route generation system in Malaysia was the motivational factor behind this project. It is a collaborative project between another final year student and me. I will be concentrating on finding the best algorithm for calculating the shortest distance between two points on a digital map. After much research into the many algorithms available, and considering some, including Genetic Algorithm (GA), the author selected Dijkstra's Algorithm (DA). This algorithm is an exact algorithm that is specifically for finding the shortest route in a network. It has been used in other networks beside roads, for instance, pipe networks or railway networks. The method used to develop this project is Rapid Application Development (RAD). Using that process, we have settled on Java as our development platform as we found it able to both implement DA and the GIS component (map display and manipulation). The software that we came up with allows the user to select a point of origin on the map and a destination point and expect the software to highlight the best route onthe map as well as output the road names in that route, from the origin to the destination. It will also give the user the total distance from origin to destination. It does not take into account the amount of time that the drivermight take to travel that distance. This project is just the first step in creating a more robust route generation system for the Malaysian market. The potential for this project to be propagated on a mobile platform can also be considered due to its Java platform.